The effects of sucrose concentrations on somatic embryogenesis of limau manis (citrus sinensis L.) - Siti Nurhazlinda, Binti Kamarudin (Universiti Malaysia Sarawak, UNIMAS, 2012)
Citrus sinensis or Limau Manis belongs to the family of Rutaceae.It is a species among most cultivated worldwide. This species can be cultivated sexually or asexually. Despite of it, the reproduction by seeds for this species leads to many problems. The species is susceptible to pathogens and diseases too. Somatic embryogenesis is one of the efficient methods in plants tissue culture for mass propagation within a short period of time. Limau Manis seeds were successfully germinated axenically in 2.0 mg/L BAP. The node and leaf segments were purposely used in this experiment. Seven different sucrose concentrations were used to identify its effects towards the development of callus and somatic embryos. Limau Manis callus were gave different growth performance towards callus induction media, 20% coconut water, 2.0 mg/L of 2,4-D and different sucrose concentration. No somatic embryo Was developed when callus were cultured on embryos induction media, 1.5 mg L-1 Kinetin + 0.1 mg L-1 NAA even after 3 months of the culture established.